تأثير الوسط الاجتماعي على الدافعية للإنجاز والتحصيل الدراسي لدى تلاميذ التعليم الثانوي التأهيلي في جهة الرباط–سلا–القنيطرة - El Mehdi Salk (International Journal of Humanities, Education, and Social Sciences, 2026)
This study aims to examine the relationship between social background, achievement motivation, and academic performance among secondary school students in the Rabat–Salé–Kénitra region of Morocco, based on socio-educational approaches emphasizing the impact of social context on school performance. A descriptive-analytical methodology was employed, and data were collected through a structured questionnaire that included students’ social and educational characteristics, academic performance over five years, patterns of family socialization, and levels of achievement motivation. The sample consisted of 283 purposively selected students (N = 283). Statistical analyses revealed a significant positive correlation between social background and academic performance (r = 0.41, p < 0.01), as well as a significant positive relationship between social background and achievement motivation (r = 0.38, p < 0.01). Moreover, a moderately strong positive correlation was found between achievement motivation and academic performance (r = 0.46, p < 0.001) at a significance level of α = 0.05, indicating that students from economically and culturally stable backgrounds exhibit higher motivation and better academic results compared to their peers from disadvantaged backgrounds. The study concludes that social background is a critical factor in explaining variations in achievement motivation and academic performance, highlighting the necessity of incorporating socio-economic considerations into educational policies to ensure fairness and educational equity.